MyFarmTrees: 6000 empowered Kenyan and Cameroonian farmers restoring 2800 hectares, expanding towards global scale-up - Chiriboga Arroyo, Fidel; Eitzinger, Anton; Ekue, Marius; Elias, Marlene; Feil, Christian; Guettou Djurfeldt, Nadia; Jalonen, Riina; Krishnan, Smitha; Oduor, Francis; Vinceti, Barbara; Kettle, Christopher (2025)
The MyFarmTrees (MFT) digital MRV platform combines mobile applications for capacity building, restoration monitoring, and digital payments. Developed through community-driven iterations in Kenya and Cameroon, MyFarmTrees has transformed tree growing and supported a network of >300 local tree nursery enterprises. MyFarmTrees users track seed collection, seedling production and tree establishment. Empowered by the platform, close to 6000 farmers have participated in the forest-landscape restoration activities using native species, and >400 stakeholders, including farmers and nursery owners, have received digital economic incentives. MyFarmTrees scales across the Global South, attracting partnerships and investments.